Traditional Chinese Medicine Protects against Cytokine Production as the Potential Immunosuppressive Agents in Atherosclerosis - Yan Ren; Wei Qiao; Dongliang Fu; Zhiwei Han; Wei Liu; Weijie Ye; Zunjing Liu (Journal of Immunology Research)
Atherosclerosis is a chronic inflammatory disease caused by dyslipidemia and mediated by both innate and adaptive immune responses. Inflammation is a critical factor at all stages of atherosclerosis progression. Proinflammatory cytokines accelerate atherosclerosis progression, while anti-inflammatory cytokines ameliorate the disease. Accordingly, strategies to inhibit immune activation and impede immune responses towards anti-inflammatory activity are an alternative therapeutic strategy to conventional chemotherapy on cardiocerebrovascular outcomes. Since a number of Chinese medicinal plants have been used traditionally to prevent and treat atherosclerosis, it is reasonable to assume that the plants used for such disease may suppress the immune responses and the resultant inflammation. This review focuses on plants that have immunomodulatory effects on the production of inflammatory cytokine burst and are used in Chinese traditional medicine for the prevention and therapy of atherosclerosis.